Engineered probiotic-mediated intratumoral delivery and controlled release of bacterial collagenase for cancer therapy - Hong-Rui Li; Bang-Ce Ye (Synthetic and Systems Biotechnology)
Elevated collagen levels within breast tumors are strongly associated with tumor progression and present a barrier to effective therapeutic agent penetration within the tumor microenvironment (TME), leading to poor clinical outcomes. To address this challenge, we engineered a probiotic strain to degrade collagen within the TME by selectively colonizing in tumors and releasing bacterial collagenase in a lysis-dependent manner. Initially, we constructed a therapeutic bacterial strain designed to lyse within the TME and release an encoded immunotoxin comprising a nanobody targeting CD47 (CD47nb) and a modified Pseudomonas exotoxin A (PE38KDEL). The introduction of collagenase-expressing bacteria, in conjunction with therapeutic immunotoxin, reduced collagen fiber levels within the TME, resulting in inhibited tumor growth and prolonged survival in a murine model of breast cancer. Furthermore, we investigated the broader applicability of the collagenase-expressing bacterial strain in combination with chemotherapeutic drugs, such as doxorubicin. Remarkably, synergistic antitumor effects were observed in mice treated with this combination therapy. In conclusion, our study demonstrates that probiotic delivery of bacterial collagenase offers a promising adjuvant treatment strategy for selectively degrading intratumoral collagen, thereby improving the efficacy of anticancer therapies in breast cancer.